S87 Relationship between bronchial reticular basement membrane thickness (RBM) and smooth muscle mass in childhood severe asthma (SA). (16th November 2010) - Bossley, C J; Regamey, N; Fleming, L; Oates, T; Lloyd, C; Bush, A; Saglani, S
Abstract : Background: In asthma there is a direct relationship between tissue eosinophilic inflammation and RBM thickness. However, relationships between components of remodelling have not been explored, but may be important especially in determining disease severity. There are no reports of an association between smooth muscle mass and asthma severity in children. We hypothesised that increases in both RBM thickness and smooth muscle mass is present in children with SA, only increased RBM thickness is present in mild asthma and neither feature is present in controls. Methods: 75 children, mean age 11.8 (5.6–17.3) years, 53 with SA, 7 with mild/moderate asthma and 15 non-asthmatic controls (bronchoscoped for upper airway symptoms) were included. All underwent fibreoptic bronchoscopy with endobronchial biopsies (EB). EB were processed to paraffin, and 5 μm sections were cut and stained with haematoxylin and eosin and used to quantify RBM thickness, epithelial shedding and volume fraction (Vv) of subepithelial smooth muscle indexed to submucosa. Results: Epithelial shedding was increased in atopic but not asthmatic subjects, (p=0.02 and p=0.37, respectively), and in children with asthma was correlated with exhaled nitric oxide (r=0.4, p=0.005). RBM thickness was increased in severe asthmatics compared to controls (p<0.0001), but a trend only to increased thickness was seen in mild asthmatics compared to controls (median (range) values: 6 (4.4–8.4) and 4 (3.1–7.5) μm, respectively; p=0.06). The Vv of subepithelial airway smooth muscle was only increased in severe asthmatics compared to controls (0.20 (0–0.65) and 0.09 (0–0.16), respectively; p=0.002). Interestingly, there was a positive relationship between RBM thickness and smooth muscle Vv fraction in asthmatics, but not in controls (r=0.31, p=0.02 and r=0.5, p=0.07, respectively) (Abstract S87 Figure 1 ). Discussion: We report for the first time a direct relationship between RBM thickness and airway smooth muscle mass in paediatric asthma. It is unknown if the relationship is causal, or both are driven by a common underlying process. Combinations of components of airway remodelling, rather than single factors, may prove to be more informative when phenotyping children with severe asthma.